Find the sum of #1^2 - 2^2 + 3^2 - 4^2 + 5^2 - 6^2........#? ( Please find out the #n^(th) term and then use the sigma method)
4 Answers
The sum is
Explanation:
The
The sum is
If
If
#S_N = -((-1)^N N(N+1))/2#
Note that this is completely general, irrespective of whether the
DERIVATION
If all the terms were adding, the sum would be:
#sum_(n=1)^(N) n^2 = 1^2 + 2^2 + . . . + N^2#
Since the series is alternating, we can write the sum to include a
#sum_(n=1)^(N) (-1)^(n+1) n^2#
#= (-1)^(2)(1)^2 + (-1)^3(2)^2 + (-1)^4(3)^2 + . . .#
#= 1^2 - 2^2 + 3^2 - . . . #
The
#S = (N(N+1))/2# .
But it's not that. We would have to account for the fact that each term alternates sign, and that means the
- If we suppose the
#N# th term is positive, then it is an odd term. That means to change its sign, we need to multiply by#(-1)^(N)# , which is guaranteed to be a#-1# multiplier. - The
#(N+1)# th term is therefore negative, and an even term. It is not affected by#(-1)^(N+1)# since#N+1# is even.
Lastly, we can rewrite our infinite sum to realize...
#sum_(n=1)^(N) (-1)^(n+1) n^2#
#= ul(-sum_(n=1)^(N) (-1)^(n) n^2)#
...that a negative sign can be factored out of everything. Thus, since
#color(blue)(S_N = -((-1)^N N(N+1))/2)#
EXAMPLE
For example, the sum up to the 3rd term is
#S_3 = -((-1)^3 3(3+1))/2#
#= 6#
And we can easily check this.
#S_3 = 1^2 - 2^2 + 3^2#
#= 1 - 4 + 9 = 6# #color(blue)(sqrt"")# .
For an even
#S_6 = -((-1)^6 6(6+1))/2#
#= -21#
And we check to see that...
#S_6 = 1^2 - 2^2 + 3^2 - 4^2 + 5^2 - 6^2#
#= 1 - 4 + 9 - 16 + 25 - 36 = -21# #color(blue)(sqrt"")#
The
#u_n = (-1)^(r+1) r^2 #
The sum of the first
# sum_(r=1)^n (-1)^(r+1) r^2 =(-1)^(n+1) \ 1/2n(n+1) #
Explanation:
We seek
# S_o = 1^2 -2^2 + 3^2 -4^2 + ... +n^2 \ \ \ \ # if#n# odd
# S_e = 1^2 -2^2 + 3^2 -4^2 + ... -n^2 \ \ \ \ # if#n# even
Or in Sigma notation:
# S = sum_(r=1)^n (-1)^(r+1) r^2 \ \ \ #
We can use the following relationship:
# -r^2 + (r+1)^2 = -r^2 + r^2+2r+1 #
# " " = 2r+1 #
# " " = r + (r+1) #
Hence we can write :
# -r^2 + (r+1)^2 -= r+ (r+1) # ..... [A]
Similarly we can write:
# r^2 - (r+1)^2 -= -(r+ (r+1)) # ..... [B]
Along with the standard summation result:
# S = sum_(r=1)^n r= 1/2n(n+1) # ..... [C]
Using the above relationship we can group terms as follows:
Case 1 :
# S_o = 1^2 -2^2 + 3^2 -4^2 + ... -(n-1)^2 + n^2 #
# \ \ \ \ = (1^2) + (-2^2 + 3^2) + ( -4^2 + 5^2) + (-(n-1)^2 + n^2) #
Using [A] this becomes:
# S_o = (1) + (2+3) + (4+5) + ((n-1)+n) #
# \ \ \ \ = 1+2+3 + ...+n #
# \ \ \ \ = 1/2n(n+1) \ \ \ # using [C]
Case 2 :
# S_e = 1^2 -2^2 + 3^2 -4^2 + ... +(n-1)^2 - n^2 #
# \ \ \ \ = (1^2 -2^2) + (3^2 -4^2) + ... +((n-1)^2 - n^2) #
Using [B] this becomes:
# S_e = (-(1+2)) + (-(3+4)) + ... +(-((n-1)+n)) #
# \ \ \ \ = -(1+2+3 ... + n) #
# \ \ \ \ = -1/2n(n+1) \ \ \ # using [C]
In summary we have:
# S_o = \ \ \ \ \1/2n(n+1) \ \ \ \ # if#n# is odd
# S_e = -1/2n(n+1) \ \ \ \ # if#n# is even
And so can readily combine these results to get the general formula:
# sum_(r=1)^n (-1)^(r+1) r^2 =(-1)^(n+1) \ 1/2n(n+1) #
See below.
Explanation:
Calling
for
and for
Resuming